Familisation and defamilisation policy in 22 European countries - Michoń, Piotr (DEMO, 2008)
High employment and activation rates have come to be hallmark of the European Union strategy. To support the economic growth and limit the negative consequences of aging societies Member States have to attract more people into employment. Breaking down the barriers to labour market entry and re-entry, especially for women who take on family responsibilities, has become some kind of signum temporis. But the problem we face is not only how to encourage women to enter the labour market but how to reconcile a number of objectives: achieving gender equity, raising fertility, lowering unemployment, increasing labour market activity, improving the well-being of children. The paper compares state policy towards working families in 22 European OECD countries and their potential consequences for women's labour market activity. It develops and uses a welfare state typology based on the theoretical concept of familisation and defamilisation. After the widely recognised Esping-Andersen's typology of welfare-state has been criticised mostly by feminist authors, scholars all over the world are looking for alternative criteria to identify models which are "gender sensitive" i.e. reflect the gender differences due to caring responsibilities. The debate led to introduce a theoretical concept of (de) familisation which concentrates on the extent to which public policy supports family in its caring function. The paper focuses on the caring function of a modern family and its consequences for women labour market activity. We identify models of state policy based on three criteria: defamilisation of care, familisation of care and defamilisation of cost of the children. The former two were used by other authors but their methods of measuring are questioned in this paper. 'Defamilisation of cost of children' measures the taxes, tools and family benefits which remain unnoticed by many authors. The typology allows the identification of variations of state policies and thus a classification of 22 European countries investigated here. (original abstract)